THE INFLUENCE OF THE WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT THE MULTI MART SUPERVISORY STORE, GISTING ATAS BRANCH, TANGGAMUS DISTRICT - Vivi Tri Wulandari; Santi Hermalia; Vicky F Sanjaya (Institut Agama Islam Negeri Kerinci, 2022)
Purpose: In the current industrial era to advance a company’s business is a must that must be done by the industry and employees so that a business can develop. That way the authors conducted research on the effect of the work environment on employee performance at a multi mart supermarket gisting atas kabupaten tanggamus, in order to find out the positive results provided by the work environment to its employees. Design/Methodology/Approach:.To get answers from the hypotheses formed, quantitative research (questionnaires) was carried out to answer the research objectives that had been prepared, namely by conducting validity tests, reliability tests, and hypotheses testing using the Smart PLS version 3 application. Findings: From hypothesis testing, it is known that all independent variables in this study have a positive effect on the dependent variable, both in terms of validity, reliability and hypotheses. Research implications: From the results of this study, it is known that a healthy work environment has a positive influence on employee performance with in the company.